2017
DOI: 10.1128/aac.00491-17
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro-In Vivo Discordance with Humanized Piperacillin-Tazobactam Exposures against Piperacillin-Tazobactam-Resistant/Pan-β-Lactam-Susceptible Klebsiella pneumoniae Strains

Abstract: Recent findings have identified Klebsiella pneumoniae strains that are pan-␤-lactam susceptible (PBL-S) but piperacillin-tazobactam resistant (TZP-R) in vitro. We assessed the efficacy of a humanized exposure of piperacillin-tazobactam (TZP) against 12 TZP-R/PBL-S K. pneumoniae isolates in an immunocompromised murine lung infection model. Discordance between the in vitro resistance profile and the in vivo efficacy of human-simulated TZP exposures against this phenotypic profile was observed. Additional studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 13 publications
2
5
0
Order By: Relevance
“…Despite these concerns, we did not identify an increase in 30-day mortality or need for ICU transfer in patients with TZP-NS/CRO-S Ec and Kp bacteremia who were empirically treated with TZP compared with those empirically treated with cephalosporins and carbapenems. This unexpected finding is consistent with those of murine pneumonia models of infection with TZP-NS/CRO-S Ec and Kp [15, 16]. In these in vivo studies, TZP exposure resulted in bacterial killing that was similar in mice infected with TZP-NS/CRO-S strains compared with those infected with TZP-S strains.…”
Section: Discussionsupporting
confidence: 88%
“…Despite these concerns, we did not identify an increase in 30-day mortality or need for ICU transfer in patients with TZP-NS/CRO-S Ec and Kp bacteremia who were empirically treated with TZP compared with those empirically treated with cephalosporins and carbapenems. This unexpected finding is consistent with those of murine pneumonia models of infection with TZP-NS/CRO-S Ec and Kp [15, 16]. In these in vivo studies, TZP exposure resulted in bacterial killing that was similar in mice infected with TZP-NS/CRO-S strains compared with those infected with TZP-S strains.…”
Section: Discussionsupporting
confidence: 88%
“…TZP resistance in this case may not translate into clinical resistance of the organism in a patient therapeutic setting, where higher concentrations of tazobactam could be obtained. In support of this theory, neutropenic mice infected with bacteria identified as TZP resistant by BMD, but susceptible to other classes of β-lactams, were successfully treated with humanized exposures of TZP ( 40 , 41 ).…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, E. coli 907355 isolates were not collected prior to and over the course of the antibiotic therapy. Future studies in mice might address whether bla TEM-1 amplification occurs in E. coli 907355 during host infection ( 40 , 41 ). Recently, McGann et al reported that aph1 amplification occurred in Acinetobacter baumanii during tobramycin treatment of an infected patient, leading to antibiotic therapy failure ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although these results are suggestive of efficacy, confirmation of their applicability and translation in the context of in vivo studies is required. In vitro-in vivo discordances have been observed previously, and thus, efficacy cannot be reliably extrapolated based on in vitro data alone (10)(11)(12). a C T , threshold concentration.…”
Section: Discussionmentioning
confidence: 99%